Double Bass Workbook for Children Focusing on Critical Thinking - Yao Lin; Pramote Danpradit (Universitas Sultan Ageng Tirtayasa, 2021)
This study aimed to create the double bass workbook that focuses on critical thinking and the efficiency of learning. studied. The research tools were: 1) The double bass workbook for children (7-9 years old), and 2) an assessment and interview form, to analyze the data was percentage. The research used that to teach those six students and gathering data by observation during the academic year 2018-2019. The findings were: The organizing music activities will make children's music lessons interesting in communication, cooperation, and critical thinking through listening, singing, game playing, recording, filling notes (adding a melody), accompanying practice to practice double bass. The teacher's assessment with the workbook was at 93% that means the teacher was highly effective in using the double bass workbook. The children passed the exam, the average score was 33 from 35. In the future, this workbook both practicability and operability.